Chelerythrine as a fluorescent light-up ligand for an i-motif DNA structure. (11th December 2020) - Chen, Hongbo; Sun, Hongxia; Zhang, Wende; Zhang, Qin; Ma, Jun; Li, Qian; Guo, Xiaomeng; Xu, Kanyan; Tang, Yalin
Abstract : A fluorescent light-up ligand for an i-motif structure has been reported in this study. Abstract : A fluorescent light-up ligand for an i-motif structure has been reported in this study. Chelerythrine (CHE) could bind to i-motif and show a significant increase in the fluorescence intensity, while exhibiting weak response towards single-stranded (ssDNA), double-stranded (dsDNA), and G-quadruplexes. This feature makes CHE advantageous in the label-free fluorescence sensing systems.